The Determinants of Carbon Dioxide Emissions in the five Asia Pacific Countries (Efficient: Indonesian Journal of Development Economics, 2022)
This research was motivated by the high contribution and growth of CO2 emissions in Asia Pacific. The study aims to analyze the influence of population, GDP per capita and hydroelectricity consumption on environmental degradation in 5 Asia Pacific countries using indicators of carbon dioxide emissions. The method used was regression analysis of panel data with the support of EViews 10 software. The Data obtained from BP Statistical Review of World Energy, World Bank and Worldometers which are combinations of cross section data, namely 5 countries in Asia Pacific region, including: China, India, Japan, South Korea and Indonesia and time series data from 2000-2019. The results of this study showed that the population, the GDP per capita and the hydroelectricity consumption has a positive effect on CO2 emissions. Penelitian ini dilatar belakangi oleh tingginya kontribusi dan pertumbuhan emisi CO2 di Asia Pasifik. Studi ini bertujuan untuk menganalisis pengaruh jumlah penduduk, PDB per kapita dan konsumsi PLTA terhadap degradasi lingkungan di 5 negara Asia Pasifik dengan menggunakan indikator emisi karbon dioksida. Metode yang digunakan adalah analisis regresi data panel dengan dukungan software EViews 10. Data diperoleh dari BP Statistical Review of World Energy, World Bank dan Worldometers yang merupakan gabungan antara data silang tempat, yaitu 5 negara di kawasan Asia Pasifik, meliputi: China, India, Jepang, Korea Selatan dan Indonesia dan data runtut waktu dari tahun 2000-2019. Hasil dari penelitian ini menunjukkan bahwa jumlah penduduk, PDB per kapita dan konsumsi PLTA berpengaruh positif terhadap emisi CO2.